Tolerance of Bentgrass (Agrostis spp.) to Postemergence Applications of Metamifop. Issue 1 (19th October 2017) - Cooper, Tyler; Beck, Leslie L.; Straw, Chase M.; Henry, Gerald M.
Abstract : Previous research indicates that metamifop may be an alternative for the control of bermudagrass ( Cynodon spp. Rich.) in bentgrass ( Agrostis spp. L.) with minimal phytotoxicity; however, only a few cultivars have been evaluated for tolerance. We hypothesize that bentgrass cultivars will respond differently to increasing rates of metamifop. Therefore, the objective of our research was to evaluate the tolerance of several bentgrass cultivars to sequential postemergence applications of metamifop. 'L‐93', 'Penn A‐4', 'Penncross', 'Seaside II', 'Crystal Bluelinks', and 'T‐1' creeping bentgrass ( Agrostis stolonifera L.) and 'SR 7200' velvet bentgrass ( Agrostis canina L.) were established in a greenhouse and sprayed with metamifop at 0, 200, 300, 400, and 500 g a.i. ha −1 . Metamifop applications reduced 3‐wk clipping production and increased phytotoxicity of L‐93, Penn A‐4, and Penncross more than Seaside II, Crystal Bluelinks, T‐1, and SR 7200 3 and 6 wk after initial treatment. Seaside II, Crystal Bluelinks, T‐1, and SR 7200 exhibited good tolerance (≤26% phytotoxicity) to sequential applications of metamifop at 300 g a.i. ha −1 . The same applications caused ≥47% phytotoxicity to the remaining cultivars. However, methods employed in this research may have affected the level of bentgrass phytotoxicity. Plants grown under greenhouse conditions are often more susceptible to herbicides and therefore exhibit higher levels of phytotoxicity. Furthermore, continuous defoliation indicative of golf course putting greens may stimulate leaf production, thereby reducing bentgrass phytotoxicity associated with metamifop applications. Consequently, additional research is warranted to evaluate the response of bentgrass cultivars maintained under putting green conditions to field applications of metamifop.